2015
DOI: 10.1111/ppa.12330
|View full text |Cite
|
Sign up to set email alerts
|

Variability and selection of verticillium wilt resistant genotypes in cultivated olive and in the Olea genus

Abstract: Developing verticillium wilt resistant genotypes is currently a major objective in olive breeding. In this study, 6017 genotypes derived from 48 crosses obtained by open pollination and crosses between olive cultivars, wild olive genotypes and other Olea species and Olea europaea subspecies were individually evaluated for verticillium wilt resistance. More than 800 genotypes were identified as resistant to the disease based on the absence of symptoms. High genetic variability and wide segregation in resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 37 publications
3
54
0
1
Order By: Relevance
“…In this sense, 'Frantoio' 9 'Arbosana' showed the highest proportion of R genotypes (38 %) while Changlot Real' 9 'Dolce Agogia' showed the highest proportion of S genotypes (81 %). These results are in concordance with previous studies (Wilhelm and Taylor 1965;Trapero et al 2015), which identified higher proportion of R genotypes in progenies from free pollination and different cross combinations including 'Frantoio' as parent. Different inheritance patterns against VW have been reported in other species such as cotton with no consensus on the genetic basis of resistance .…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…In this sense, 'Frantoio' 9 'Arbosana' showed the highest proportion of R genotypes (38 %) while Changlot Real' 9 'Dolce Agogia' showed the highest proportion of S genotypes (81 %). These results are in concordance with previous studies (Wilhelm and Taylor 1965;Trapero et al 2015), which identified higher proportion of R genotypes in progenies from free pollination and different cross combinations including 'Frantoio' as parent. Different inheritance patterns against VW have been reported in other species such as cotton with no consensus on the genetic basis of resistance .…”
Section: Discussionsupporting
confidence: 95%
“…For each cross, white circle and triangle represent values for female and male parents, respectively out under controlled conditions in the present work. This procedure may represent some advantages compared to selection at the seedling stage previously reported (Wilhelm and Taylor 1965;Trapero et al 2015). On the one hand, the possibility of replication of plant materials, instead of one single plant per genotype, allows more accurate evaluation for disease resistance.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This study used Frantoio olive as a resistance reference because of its resistance to D. V. dahliae and current commercial interest (López‐Escudero et al ., ; Barranco, ; Bubici & Cirulli, ; Arias‐Calderón et al ., ; Trapero et al ., ). Unlike the wild olive clones, incipient symptoms developed in Frantoio olives, with incidence varying from 20 to 60% depending on inoculation methods and experiments, which agrees with reports by other authors (Martos‐Moreno et al ., ; Cirulli et al ., ; Bubici & Cirulli, ; Gramaje et al ., ; Arias‐Calderón et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Wild olive genotypes highly resistant to D V. dahliae used as rootstocks can provide an improved means for the management of verticillium wilt in grafted susceptible olive cultivars that are agronomically adapted and commercially desirable (Jiménez‐Díaz et al ., ; Trapero et al ., , ; Arias‐Calderón et al ., ). In previous studies, it was concluded that wild olive clones Ac‐13, Ac‐18, OutVert and StopVert are highly resistant to D V. dahliae based on the development of incipient or no foliar disease symptoms, together with reduced stem vascular browning and reisolation of the fungus (Colella et al ., ; Jiménez‐Díaz, ; Bubici & Cirulli, ).…”
Section: Discussionmentioning
confidence: 99%